Guía de práctica clínica para el tratamiento de leucemia linfoblástica aguda en pacientes pediátricos - Zapata López, Arturo Manuel (2025)
Introduction: This article summarizes the clinical practice guideline (CPG) for the treatment of acute lymphoblastic leukemia in pediatric patients. Objective: To provide health professionals with evidence-informed recommendations for the treatment of acute lymphoblastic leukemia in pediatric patients. Methods: A guideline development group (GDG) was formed, including medical specialists and methodologists, which formulated 7 clinical questions. Systematic searches for systematic reviews and –when considered pertinent– primary studies were conducted in PubMed, Central, and Lilacs during June-August 2024. Evidence was selected to answer each of the clinical questions posed. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the GDG used the GRADE methodology to review the evidence and formulate the recommendations, good clinical practice points, and flowcharts. Finally, the GPC was approved by Directorial Resolution No. 008-2024-CETS/INS. Results: This GPC addressed 7 clinical questions, and 5 conditional recommendations, 4 points of good clinical practice, a recommendation in favor resulting from a health technology assessment (HTA), and 4 flowcharts were formulated. Conclusion: Evidence-based recommendations were issued for the treatment of acute lymphoblastic leukemia in pediatric patients.